Instilling QoS in Wireless Sensor Networks - Samara, Kamil; Hosseini, Hossein (Discoveries in Agriculture and Food Sciences, 2017)
Wireless Sensor Networks (WSNs) have been a desired choice for monitoring and automatic control of remote and unreachable objects and environments due to their low cost. However, such deployment requires quality-of service (QoS) techniques to assure reliable performance. Furthermore, provision of QoS in WSNs is a challenging task due to hardware limitations. A cross-layer approach is a promising option where information from different layers can be used to make QoS decisions. In this paper, we present a routing protocol where information from the application layer is used to make differentiated routing decisions based on data packets classifications. In our case, data packets are classified into: normal, urgent, and critical. Based on this classification each data packet class is treated differently by storing each data packet class in a designated buffer. Different buffers will have different routing priority decided by the protocol designer.